Antimalarial Activity of Ethanol Extract of Kelakai Leaves (Stenochlaena palustris) to Parasitemia and Splenomegaly in BALB/c Mice Infected with Plasmodium berghei ANKA - Laily Nur Azizah; Puspa Wardhani; Heny Arwati (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2022)
Introduction: Malaria is one of global health problems. Splenomegaly is one of malaria symptoms. Antimalarial drug resistance had been reported. Alternative treatment is by using traditional medicinal plants such as kelakai (Stenochlaena palustris). Kelakai contains alkaloid and flavonoid which had been reported to have antimalarial activity. The aim of this study was to discover antimalarial activity of ethanol extract of kelakai leaves to parasitemia and splenomegaly of Plasmodium berghei ANKA in infected BALB/c mice.Methods: This study was based on a modified Peter test using BALB/c mice infected with P. berghei ANKA treated with ethanol extract of kelakai leaves, with chloroquine diphosphate as a positive control. The negative control was P. berghei ANKA infected mice without any additional treatment. Administration of ethanol extract of kelakai leaves was performed for 4 days with a serial doses of 100, 10, and 1 mg/kg body weight. The positive control was given chloroquine diphosphate 20 mg/kg body weight. Parasitemia was observed daily prior to the calculation of the percentage of parasite growth and parasite growth inhibition. At the end of the test, the mice were sacrificed and spleens were isolated to measure their sizes. Probit analysis was performed to obtain ED50 to find the effect of extract in parasite killing by 50%. Spearman test was performed to analyze the correlation of doses of extract and splenomegaly.Results: Parasitemia growth inhibition was directly proportional to the dose. Higher parasitemia inhibition was obtained at higher doses and vice versa. Result of probit analysis showed an ED50 was 77.05 mg/kg body weight. Statistical analysis resulted in insignificant correlation between doses and splenomegaly p = 1.0 (significancy < 0.05).Conclusion: Ethanol extract of kelakai leaves possessed good antimalarial activity and there was no correlation between extract doses and splenomegaly in Plasmodium berghei ANKA-infected mice.